The impact of treatment on the psychological burden of mothers of children with chronic hepatitis C virus infection: a multicenter, questionnaire survey - Tomoya Fukuoka; Kazuhiko Bessho; Satoyo Hosono; Daiki Abukawa; Tatsuki Mizuochi; Koichi Ito; Jun Murakami; Hideo Tanaka; Yoko Miyoshi; Tomoko Takano; Hitoshi Tajiri (Scientific Reports, 2022)
Abstract Mothers of children with chronic hepatitis C virus (HCV) infection experience anxiety about the health of their children. In this study we assessed an impact of treating children with chronic HCV infection on the psychological burden of their mothers. This was a multicenter, questionnaire survey conducted at six institutions in Japan. A newly-developed questionnaire for this study was used to assess changes in the mothers’ various concerns regarding HCV infection and thoughts about their child’s HCV infection. Responses at the time of diagnosis and at the time of the survey were compared between mothers of children who had received treatment and those without treatment. Responses were received from 36 of 37 eligible mothers (11 and 25, non-treatment and treatment groups, respectively). All children in treatment group had successfully eliminated the virus. Mothers in both groups were psychologically stressed in various ways, including concern about their child’s health in the present and future at the time of diagnosis, concern about school, employment, and marriage, concern about the behavior of others towards them and infecting others with HCV, and feelings of guilt regarding their child. These concerns were significantly lower in the present compared to at the time of diagnosis in treatment group, and the rate of decrease was significantly higher in treatment group compared to non-treatment group. Successful treatment greatly reduced mothers’ concerns about their children’s HCV infection, indicating that treatment during childhood is beneficial from the perspective of the mothers’ psychological burden.